South Africa and national TB control: Are we making progress? - Gboyega A Ogunbanjo (South African Family Practice)
South Africa accounts for the worst global tuberculosis epidemics fuelled by the spread of HIV infection. The tuberculosis (TB) incidence increased from 300 per 100,000 people in the early 1990s to more than 950 per 100,000 in 2012.1 In addition, the country remains one of the countries with the highest TB burden globally, with the World Health Organisation (WHO) statistics giving an estimated incidence of 454,000 cases of active TB in 2015.2 This means that about 0.8% of South Africa’s population of 54 million develop active TB disease annually. Of the 454 000 TB cases in South Africa in 2015, WHO estimated that about 57% (258,000) were HIV positive. It also estimated that of 157,505 whose status was known, and who were known to be HIV positive, some 85% (133,116) were on antiretroviral therapy.3 From the same 2015 report, Eastern Cape, KwaZulu-Natal and Western Cape provinces had the highest incidence rates of 692, 685 and 681 per 100,000 respectively. The most notable decline was in KwaZulu-Natal where the incidence decreased from 1,185 to 685 per 100,000 over the last five years.1